2013
DOI: 10.4300/jgme-d-11-00314.1
|View full text |Cite
|
Sign up to set email alerts
|

Pediatrics Residents' Perspectives on Family-Centered Rounds: A Qualitative Study at 2 Children's Hospitals

Abstract: Background Many academic hospitals have incorporated family-centered rounds, yet little is known about pediatrics residents' perspectives on the educational impact of these rounds. Objective To identify pediatrics residents' knowledge, attitudes, and beliefs about family-centered rounds, including perceived benefits and barriers. Methods We conducted focus gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 14 publications
0
32
0
Order By: Relevance
“…13 Parental participation during rounds offers a venue to meet the Accreditation Council for Graduate Medical Education's core competencies of professionalism, interpersonal and communication skills, direct observation, and feedback. 1,[14][15][16] Physician trainees reported that family-centered rounds enhanced their medical education by increasing the number of encounters with patients and observations of direct patient care, providing an opportunity for real-time feedback and role modeling by attending physicians, and enhancing communication and interpersonal skills. 16 Parental participation during rounds has been embraced as a measure of quality and as standard practice recommended by the American Academy of Pediatrics.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13 Parental participation during rounds offers a venue to meet the Accreditation Council for Graduate Medical Education's core competencies of professionalism, interpersonal and communication skills, direct observation, and feedback. 1,[14][15][16] Physician trainees reported that family-centered rounds enhanced their medical education by increasing the number of encounters with patients and observations of direct patient care, providing an opportunity for real-time feedback and role modeling by attending physicians, and enhancing communication and interpersonal skills. 16 Parental participation during rounds has been embraced as a measure of quality and as standard practice recommended by the American Academy of Pediatrics.…”
mentioning
confidence: 99%
“…1,[14][15][16] Physician trainees reported that family-centered rounds enhanced their medical education by increasing the number of encounters with patients and observations of direct patient care, providing an opportunity for real-time feedback and role modeling by attending physicians, and enhancing communication and interpersonal skills. 16 Parental participation during rounds has been embraced as a measure of quality and as standard practice recommended by the American Academy of Pediatrics. 3 The purpose of this quality improvement project was to increase the percentage of invitations to participate in morning rounds on the pediatric cardiothoracic intensive care unit (CTICU) that were extended to the parents available.…”
mentioning
confidence: 99%
“…2,3 In addition, fear of sharing sensitive patient information on FCR also serves as a barrier because trainees attempt to balance the emotional needs of patients and families with the need for frank clinical discussion. 2,4 Anecdotally, this is particularly true when it comes to discussion of appropriate differential diagnoses, especially when a difficult diagnosis such as malignancy is possible. These fears often lead to a modified presentation of the patient's clinical picture, with more emphasis placed on patient and family comfort than trainee education.…”
mentioning
confidence: 99%
“…Although resident discomfort and time constraints are consistently recognized as the greatest barriers to teaching, studies have cited attending style as the key factor in determining residents' satisfaction with their educational experience. [2][3][4]6 Although it would be difficult to standardize rounding, further study to identify specific skills that promote educationally effective FCR could allow for training in these areas. We believe that skills such as bedside physical examination teaching, effective communication, and encouragement of trainee autonomy would be viewed by residents as strengths of educationally stimulating attending physicians.…”
mentioning
confidence: 99%
See 1 more Smart Citation